PEMBERDAYAAN KUBE FAKIR MISKIN MELALUI MEKANISME BANTUAN LANGSUNG PEMBERDAYAAN SOSIAL (BLPS) Studi Evaluasi tentang Bantuan Langsung Pemberdayaan Sosial di Desa Sendangsari, Kecamatan Minggir, Kabupaten Sleman, Yogyakarta - , Dra. Endang Iriyanti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
KUBE empowerment programs through mechanisms help poor people Social Empowerment is a program of the National Policy Ministry of Social Affairs in order to evaluate the relief which has for years implemented through partners. Live Help Social Empowerment is a mechanism of social assistance or stimulant fund productive economic efforts to social welfare problems or poor families are channeled directly to the KUBE has been established by the Ministry of Social Affairs. Poor People Empowerment Program through a Joint Business Group (KUBE) with Productive Economic Enterprises (UEP) is designed in accordance with the potential of poor communities to improve the welfare of the poor to advance economically and socially. One of the locations that receive assistance programs of empowerment through the mechanism of Direct Social Empowerment is in the Sendangsari,Village Minggir District, Sleman Regency. Therefore, the study wanted to evaluate on KUBE empowering the poor through mechanisms of Direct Social Empowerment. This type of research is a descriptive qualitative evaluative approach. The method is a post-program evaluation is an evaluation conducted after the program is completed. Sources of data in this study is the statement and the board members determined purposive KUBE sampling and secondary data is data about the Live Help Social Empowerment and profile locations, informants and KUBE. Data collection techniques used were interviews, observation and documentation. Data analysis techniques implemented by way of reduction, data display and verification and conclusion. The results showed the process of implementation of the empowerment of poor through mechanisms KUBE poor live Help Social Empowerment in the Sendangsari Village, Minggir District, Sleman Regency have not run in accordance with the guidelines that have been determined. Although the stages in the process of empowerment which consists of pre empowerment, preparation, implementation, monitoring and evaluation and out come of empowerment have been conducted but the results canât be perceived by members of KUBE. Assistance for business development KUBE is positioned as a long-term savings and improve the social status that will be to provide for education and other needs. In conclusion, the empowerment of the poor through mechanisms KUBE Help Social Empowerment is a strategy used by the government in implementing empowerment of poor families. This strategy shaped the flow of cash and capital assistance directly to the KUBE who manages the business economically productive group. There was no increase of in come, even the work done did not experience a significant development. Level of welfare of members has not changed but with the help of capital that has received an increase in assets even though very minimal. The results suggest that empowerment KUBE help the poor people through Social Empowerment should the need for assistance on an ongoing basis and during the implementation process needs to intensified in monitoring and evaluated regularly and periodically until the post-empowerment.